2013
DOI: 10.1007/s10995-013-1425-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education and Perinatal Outcomes Among Spanish Women Residing in Southern Spain (2001–2011)

Abstract: Evidence suggests that educational differences in perinatal outcomes have increased in some countries (Eastern Europe) while remained stable in others (Scandinavian countries). However, less is known about the experience of Southern Europe. This study aims to evaluate the association between maternal education and perinatal outcomes derived from birthweight (low birthweight and macrosomia) and gestational age (pre-term and post-term births) among Spaniards living in the Autonomous Community of Andalusia during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 30 publications
1
39
1
Order By: Relevance
“…In this study, we noted that a tertiary educated and employed mother had a greater LBW risk during the economic contraction. Contrary to our result, another study reports that women with higher education had lower risk of LBW after the onset of the economic crisis in Andalusia, Spain; an area accounting for 19% of births in the country 39. The variation in maternal social characteristics, health behaviours and health system may explain the differences in maternal educational gradient and LBW relationship for Portugal and Spain during the recession.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we noted that a tertiary educated and employed mother had a greater LBW risk during the economic contraction. Contrary to our result, another study reports that women with higher education had lower risk of LBW after the onset of the economic crisis in Andalusia, Spain; an area accounting for 19% of births in the country 39. The variation in maternal social characteristics, health behaviours and health system may explain the differences in maternal educational gradient and LBW relationship for Portugal and Spain during the recession.…”
Section: Discussioncontrasting
confidence: 99%
“…The most rigorous study of birth outcomes found that the announcement of mass layoffs (an indicator of fear or stress related to the economy) was associated with declines in birthweight even prior to actual layoffs [17]. Evidence from Spain suggested that maternal educational inequalities in adverse birth outcomes may have increased during the Recession [18]. Another study in Spain was more mixed; it found that while prevalence of child overweight/obesity increased, children’s health-related quality of life improved [19].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from the E.U. suggested widening inequalities in birth outcomes, smoking behavior, and SRH [18, 48, 87, 91], but further inquiry into the impact of the Recession on socioeconomic and racial/ethnic disparities in health outcomes—especially in the U.S.—remains an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…As this meta-analysis pooled data from observational studies, it is possible AMA is linked to adverse fetal outcome(s) by confounding factors which were not measured by this analysis. Interestingly, women over the age of 35 are more likely to have higher levels of education, higher income, and are more likely to be employed and attend prenatal classes, all of which reduce the risk of adverse pregnancy outcomes (12,13). Thus, despite these favourable characteristics, AMA still appears to be an independent risk factor for adverse fetal outcome(s).…”
Section: Relationship Between Ama and Adverse Fetal Outcomesmentioning
confidence: 99%